Combined Treatment of a Gallbladder Volvulus with a Common Bile Duct Obstruction. (30th April 2017) - Laydi, M.; Charpentier, K.; Paquette, B.; Heyd, B.
Abstract : Gallbladder volvulus is a rare disease and can lead to an acute cholecystitis. We report the case of an elderly woman with a gallbladder volvulus, diagnosed at CT scan and treated by surgery and endoscopic sphincterotomy.